2018
DOI: 10.1002/rcm.8227
|View full text |Cite
|
Sign up to set email alerts
|

Ion formation in droplet‐assisted ionization

Abstract: The results are consistent with other inlet ionization techniques, suggesting that similar ion formation mechanisms are operative. Optimized ion yields (the combined effects of ionization probability and ion transmission) for DAI are currently in the 10 to 10 range, which is sufficient for many aerosol applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 28 publications
3
46
0
Order By: Relevance
“…16 In a subsequent study, the role of droplet size was explored for liquid droplets composed of poly(propylene glycol) (PPG). 17 In this experiment, PPG served both as the analyte and the solvent, and it was shown that the ion signal intensity scaled approximately with d 4 , where d = droplet diameter. This result suggested that droplet size as well as analyte mass flow affects the ion signal.…”
Section: ■ Results and Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…16 In a subsequent study, the role of droplet size was explored for liquid droplets composed of poly(propylene glycol) (PPG). 17 In this experiment, PPG served both as the analyte and the solvent, and it was shown that the ion signal intensity scaled approximately with d 4 , where d = droplet diameter. This result suggested that droplet size as well as analyte mass flow affects the ion signal.…”
Section: ■ Results and Discussionmentioning
confidence: 77%
“…Salt contamination has been noted previously. 16,17 In separate MSMS experiments, cluster ions were examined by ramping the collision energy. Only a very low collision energy (<10 eV) was needed to break apart the clusters, showing that they are noncovalently bound.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…73 This group also conducted fundamental research relating to these processes. 74 retrofitted a 266 nm laser on a high-vacuum time-of-flight (TOF) mass spectrometer and produced ESI-like charge states of insulin using 3-NBN as matrix, while the typical 355 nm laser experiments failed to produce analyte ions. 33 The matrix 3-NBN has absorption at 266 nm so that one must expect that the thermal energy required for new ionization processes operated under high vacuum is placed into the system through the use of a laser under these nearly collision-free conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The Johnston group developed droplet‐assisted inlet ionization for aerosol analysis applying an inlet tube heated as high as 850 °C without observing analyte fragmentation 73 . This group also conducted fundamental research relating to these processes 74 . In collaborative work, Ni (Academia Sinica, Taipei, Taiwan) and Weidner (Federal Institute for Materials Research and Testing, Berlin, Germany) retrofitted a 266 nm laser on a high‐vacuum time‐of‐flight (TOF) mass spectrometer and produced ESI‐like charge states of insulin using 3‐NBN as matrix, while the typical 355 nm laser experiments failed to produce analyte ions 33 .…”
Section: Introductionmentioning
confidence: 99%